Facile Preparation of Highly Enantioenriched 1,4-Benzothiazin-3-ones by the Substitution of α-Bromoacetate with 2-Aminothiophenol - Lee, Ji Su; Lee, So Jeong; Han, Gun Hee; Park, Yong Sun (Synlett, 2023)
A simple and convenient approach for highly enantioenriched 2-substituted 1,4-benzothiazin-3-ones was developed via the nucleophilic substitution of α-bromoacetates derived from either l-threonate or l-serinate using 2-aminothiophenol and a subsequent facile lactamization.
Keywords: 1,4-benzothiazin-3-one; carbon–sulfur bond formation; dynamic resolution; asymmetric synthesis; chiral auxiliaries; lactamization